Real-time in situ dynamic sub-surface imaging of multi-component electrodeposited films using event mode neutron reflectivity. (13th July 2018) - Hillman, A. Robert; Barker, Robert; Dalgliesh, Robert M.; Ferreira, Virginia C.; Palin, Emma J. R.; Sapstead, Rachel M.; Smith, Emma L.; Steinke, Nina-Juliane; Ryder, Karl S.; Ballantyne, Andrew D.
Abstract : We investigate the deposition, evolution and dissolution of single and two-component metal layers on Au substrates immersed in the deep eutectic solvent Ethaline. Abstract : Exquisite control of the electrodeposition of metal films and coatings is critical to a number of high technology and manufacturing industries, delivering functionality as diverse as anti-corrosion and anti-wear coatings, electronic device interconnects and energy storage. The frequent involvement of more than one metal motivates the capability to control, maintain and monitor spatial disposition of the component metals, whether as multilayers, alloys or composites. Here we investigate the deposition, evolution and dissolution of single and two-component metal layers involving Ag, Cu, and Sn on Au substrates immersed in the deep eutectic solvent (DES) Ethaline. During galvanostatically controlled stripping of the metals from two-component systems the potential signature in simultaneous thickness electrochemical potential (STEP) measurements provides identification of the dissolving metal; coulometric assay of deposition efficiency is an additional outcome. When combined with quartz crystal microbalance (QCM) frequency responses, the mass change : charge ratio provides oxidation state data; this is significant for Cu in the high chloride environment provided by Ethaline. The spatial distribution (solvent penetration and external roughness) of multiple components in bilayer systems is provided by specular neutron reflectivity (NR). Significantly, the use of the recently established event mode capability shortens the observational timescale of the NR measurements by an order of magnitude, permitting dynamic in situ observations on practically useful timescales. Ag, Cu bilayers of both spatial configurations give identical STEP signatures indicating that, despite the extremely low layer porosity, thermodynamic constraints (rather than spatial accessibility) dictate reactivity; thus, surprisingly, Cu dissolves first in both instances. Sn penetrates the Au electrode on the timescale of deposition; this can be prevented by interposing a layer of either Ag or Cu.